Literature Review: Hubungan Kepercayaan dan Sosial Budaya terhadap Pemberian Air Susu Ibu Eksklusif pada Bayi - Rahmawati, Windi Chusniah; Permata, Fedina Dyah Ayu; Nasrullah, Mohammad Naufal; Sawitri, Nabila Dwi; Yulyantika, Nadya Rindy; Nizar, Qonita Qotrunnada; Putri, Salsabilla Meidiana (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
In Indonesia, maternal and child health problems related to health culture are still very concerning. One community culture that can impact maternal and child health and is a difficult problem to solve is the many myths related to exclusive breastfeeding. The number of myths circulating is an obstacle to improving the quality of maternal and child health. Therefore, this study aims to determine the relationship of beliefs and socio-culture to exclusive breastfeeding in infants. The writing of the article uses the literature review method with the source of the article coming from the Google Scholar database. The articles obtained and in accordance with the criteria were 5 national articles which were then reviewed. The results showed that there was a relationship between beliefs and socio-culture towards exclusive breastfeeding in infants. There are several social and cultural factors that influence exclusive breastfeeding practices in Indonesia, including belief in myths, traditions, family support, education level, maternal knowledge, and employment status.